The Role of Urban Space in Wardah's TV Advertisement - Putra, Yoga Mestika; Triandana, Anggi (Prosiding Seminar Nasional Humaniora, 2025)
This study deals with the role of urban space in mass media, especially in television. The purpose of the research is to describe the role of urban space in television advertising in forming the position of the product to the audience. The questions deal with the sign space. Besides visual and audio elements, television also has dynamic movements. This research looks at the role of urban space in the media, especially television. The aim of the study is to describe the role of urban space in television advertising to build a product position in the audience. The questions are about how sign space (ie the space in front of the signer's body) is used to position a structure. The data used in this study comes from a TV commercial in 2013. This study is a qualitative study conducted using semiotic analysis. The result shows that with the help of the codes of the urban space, it was possible to build Wardah as a skin protection, whitening, and moisturizing product for urban girls. The result shows that advertising gives consumers much more information about the products and also influences them to buy the products.